2001
DOI: 10.1177/000348940111000714
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Serum Immunoglobulins and Antibodies to Pneumococcal Capsular Polysaccharides in Patients with Recurrent or Chronic Sinusitis

Abstract: A study was carried out to search for underlying immunoglobulin deficiencies in 25 patients with recurrent or chronic sinusitis. The mean duration of the patient histories of recurrent or chronic sinusitis was 7.2 years. Concentrations of serum immunoglobulins and specific pneumococcal antibodies were measured in the patients and in 25 age- and sex-matched control individuals. The mean serum IgA concentration (1.6 g/L) was lower in the patients than in the control individuals (2.1 g/L, p = .024). On the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 19 publications
(6 reference statements)
2
26
0
1
Order By: Relevance
“…[585][586][587][588][589] An association between hypoimmunoglobulinemia and CRS has been described in the literature and multiple studies have demonstrated PID as a risk factor for the development of CRS. 15,155,[590][591][592][593][594][595][596] The association is further strengthened by other studies that show an increased incidence of RS in patients with immune dysfunction. 586,587 CVID, X-linked hypogammaglobulinemia, and several other disorders of humoral immunity are frequently referenced as contributing factors to chronic or recurrent recalcitrant RS.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…[585][586][587][588][589] An association between hypoimmunoglobulinemia and CRS has been described in the literature and multiple studies have demonstrated PID as a risk factor for the development of CRS. 15,155,[590][591][592][593][594][595][596] The association is further strengthened by other studies that show an increased incidence of RS in patients with immune dysfunction. 586,587 CVID, X-linked hypogammaglobulinemia, and several other disorders of humoral immunity are frequently referenced as contributing factors to chronic or recurrent recalcitrant RS.…”
Section: Discussionmentioning
confidence: 83%
“…586,587 CVID, X-linked hypogammaglobulinemia, and several other disorders of humoral immunity are frequently referenced as contributing factors to chronic or recurrent recalcitrant RS. 15,588,589,[596][597][598][599] A number of selective Ig deficiencies, specifically those involving IgG3 subclass, IgA, and IgM, have been consistently identified in this group of patients. 585,586,590,593,594,[596][597][598][600][601][602] Preimmunization antipneumococcal titers have been shown to be decreased as well, particularly in patients with the more severe forms of immunodeficiency such as CVID.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…164 The majority of immunodeficient patients with recurrent sinusitis have defects in humoral immunity; however, patients with other types of immune defects might present with recurrent sinusitis, such as patients with AIDS who have combined humoral and cellular impairments. [165][166][167][168] The indications for pursuing an immunodeficiency evaluation depend on the age, medical history, physical examination, and lifestyle of the patient. For example, in an infant of less than 2 years of age with recurrent and lifethreatening infections of the sinuses and other organs, one should pursue this evaluation in an expeditious manner.…”
Section: Summary Statementsmentioning
confidence: 99%
“…[4][5][6] Multiple studies have demonstrated primary immunodeficiency as a risk factor for the development of CRS. 2,[7][8][9][10][11][12][13][14][15][16][17] The association is further strengthened in that other studies show an increased incidence of sinusitis in patients with immune dysfunction. 5,6 Appropriate evaluation for primary immunodeficiency may include quantitative serum immunoglobulins and specific antibody responses.…”
mentioning
confidence: 99%